POTENSI PENGEMBANGAN BLOK SEGITIGA TUNJUNGAN SEBAGAI BAGIAN DARI PEMBENTUK CITRA KOTA - Bramasta Putra Redyantanu (ATRIUM: Jurnal Arsitektur, 2017)
Title: Potential Development of Tunjungan Triangle Blocks As Part of Image of The CityMaker Good urban space is created from a good urban planning also. In the planning phase of the city, it is simulated how a good city consists of well synchronized urban components. Tunjungan, as one of the important formers of Surabaya character, is the most dynamic developed block. The gap between good planning and real condition, was become larger due to partially development. The diversity of land ownership, the capabilities of each developer and so on, are some of the causes. Yet the success of an urban architectureis affected by the ability of spatial planning and city planning collectively.Integrated development involving all aspects of urban space constituency is something that is expected to happen. This study attempted to read the conditions of the triangular block of Tunjungan from urban planning theory perspectives, then reflected on the real conditions in the field. The goal is to get a recommendation based on the development potential of urban elements that will strengthen the identity of the city of Surabaya itself.